Introduction and Use of Technology Applications to Improve Student Learning at SMP Negeri 3 Siborongborong - Rekolina Siahaan; Novita C. Hutabarat (International Journal of Community Engagement and Development, 2023)
The use of technology in education has become a necessity in the current digital era. Especially for junior high school students, it is important to understand and utilize technology applications effectively in the learning process. This community service aims to develop a community service program that focuses on introducing and utilizing technology applications to improve junior high school students' learning. Methods for developing this program include literature study, field observations, and direct interaction with junior high school students and teachers. This community service program is designed to provide middle school students with an in-depth understanding of various technology applications that are relevant to their learning. Apart from that, this program also aims to train students in using these applications productively and creatively in a learning context. An interactive and participatory approach is implemented at every stage of the program, so that students not only become passive consumers of technology, but also become producers of educational content. Initial evaluation results show a positive response from students and teachers to this program. Students reported increased interest and motivation in learning, as well as increased understanding of subject matter through the use of technology applications. Meanwhile, teachers reported positive changes in student participation and involvement in the learning process. Thus, it is hoped that this community service program can become an effective model in introducing and utilizing technology applications to improve junior high school students' learning. The practical implication of this program is that there is an increase in students' digital skills and an increase in the quality of learning in the school environment.